A new species of Craterostigma (Linderniaceae) from Kenya - Darbyshire, Iain; Fischer, Eberhard (Phytotaxa, 2017)
The new species Craterostigma loitense from the Loita Hills in Kenya is described and illustrated. It differs from Craterostigma purpureum in the two abaxial staminodes, the basal tufts of hairs on the anthers, and the subentire to serrulate leaf margin.